Smartphone based non invasive real time white blood cell counter leveraging blue light and static magnetic field - Nafi Us Sabbir Sabith; Masud Rabbani; Kazi Shafiul Alam; Sheikh Iqbal Ahamed (Scientific Reports)
Abstract White blood cells (WBCs), also known as leukocytes, are one of the most significant parts of the immune system. They generate antibodies, protect the body from illnesses, and heal wounds. Accurate estimation of WBCs is key for diagnosing cancer, infections, leukemia, lymphoma, and other diseases. However, the widely used Complete Blood Count (CBC) test presents challenges, including prick anxiety, discomfort, and logistical inconvenience to patients. This study introduces a ubiquous White Blood Cell counting system, UbiWhite, a novel smartphone-based, non-invasive system for real-time WBC counting from fingertip videos. Our system uses optical and magnetic techniques to provide accurate WBC counts without blood extraction. An initial experimentation was carried out on 20 adult participants to verify the system’s effectiveness compared to standard CBC tests (IRB #4051). The developed algorithms exhibit 1.04 and 1.23 RMSE, respectively. Our innovation provides an easy, affordable, and instantaneous solution for monitoring WBCs in various healthcare settings, including homes and critical care units. Additionally, it serves as a beacon of hope for low- and middle-income nations, where access to and affordability of traditional lab tests are limited.